GEHLEN ORGANIZATION AND THE NAZIS - REDJEB, BADIS BEN (ROUTLEDGE, 2026)
This book uncovers the extent to which the Gehlen Organization, the intelligence organization created by the United States at the end of World War Two, recruited and used controversial individuals who had been heavily involved in the atrocities committed by the Nazis.Through an extensive study of records and primary sources, including the archives of the German armed forces during the Nazi era and the declassified files of the U.S. Army, as well as of several intelligence organizations such as the Central Intelligence Agency and the Intelligence Service of the Federal Republic of Germany, the book investigates the war record of individuals who were recruited by the Gehlen Organization. This investigative work proves that several General Staff officers hired had a dark past and that the organization ultimately served as a safe haven for many Nazis. The book provides a new and original perspective on essential events that took place at the end of World War Two, thereby contributing to a new interpretation of history.While all readers interested in historical accuracy will find this book of interest, The Gehlen Organization and the Nazis is crucial reading for students researching Nazi Germany, the early Cold War, intelligence studies, and postwar German history.